1996
DOI: 10.1128/iai.64.12.5373-5383.1996
|View full text |Cite
|
Sign up to set email alerts
|

Nonopsonic binding of Mycobacterium tuberculosis to human complement receptor type 3 expressed in Chinese hamster ovary cells

Abstract: Nonopsonic invasion of mononuclear phagocytes byMycobacterium tuberculosis is likely important in the establishment of a primary infection in the lung. M. tuberculosis binds to a variety of phagocyte receptors, of which the mannose receptor and complement receptor type 3 (CR3) may support nonopsonic binding. CR3, a ␤ 2 integrin, is a target for diverse intracellular pathogens, but its role in nonopsonic binding remains uncertain. We have examined the binding of M. tuberculosis H37Rv to human CR3 heterologously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 36 publications
6
48
0
1
Order By: Relevance
“…A similar strong reduction in CD11b expression was reported in CF human monocytes and was associated with a reduced capacity of monocytes to phagocytose opsonized P. aeruginosa [61]. Previous studies have also shown the nonopsonic ingestion of microbial pathogens, such as Mycobacterium tuberculosis [62,63] Leishmania [64], and P. aeruginosa [65] through CR3-mediated phagocytosis. Also defects in the chemoattractants mediated activation of integrins have been documented in CF human and murine monocytes [66].…”
Section: Alteration Of Pattern Recognition Receptors In Cf Macrophagessupporting
confidence: 74%
“…A similar strong reduction in CD11b expression was reported in CF human monocytes and was associated with a reduced capacity of monocytes to phagocytose opsonized P. aeruginosa [61]. Previous studies have also shown the nonopsonic ingestion of microbial pathogens, such as Mycobacterium tuberculosis [62,63] Leishmania [64], and P. aeruginosa [65] through CR3-mediated phagocytosis. Also defects in the chemoattractants mediated activation of integrins have been documented in CF human and murine monocytes [66].…”
Section: Alteration Of Pattern Recognition Receptors In Cf Macrophagessupporting
confidence: 74%
“…This is consistent with previous ¢ndings of opsonized Rhodococcus equi binding to CHO-Mac-1 cells [40] and suggests that the iC3b binding site in the I domain of CR3 is functional. CR3 on CHO-Mac-1 cells can also mediate non-opsonic binding of Mycobacterium tuberculosis [41], apparently to the L-glucan lectin site of CR3 via a cation-independent mechanism [42]. Taken together, these results suggest that CR3 on CHO-Mac-1 cells was abundantly expressed in an active ligand binding conformation.…”
Section: Discussionmentioning
confidence: 97%
“…As if it were not enough for M. tuberculosis to acquire opsonic C3 peptides by at least two distinct mechanisms, M. tuberculosis can bind to CR3 at two distinct sites on the receptor. Opsonized M. tuberculosis binds CR3 at its C3bi binding domain, and nonopsonized M. tuberculosis uses its endogenous capsular polysaccharides to interact with the ␤-glucan binding site near the C terminus of CD11b (9,10). Experiments using human monocytes and murine macrophages had strongly implied that there is more than one mode of interaction between M. tuberculosis and CR3 (31,37), but unambiguous evidence that nonopsonic (i.e., C3bi-independent) interactions occur was obtained in studies in which CR3 was expressed in a nonmacrophage background, so that endogenous synthesis of C3 by macrophages could not interfere.…”
Section: Complement Receptorsmentioning
confidence: 99%
“…Experiments using human monocytes and murine macrophages had strongly implied that there is more than one mode of interaction between M. tuberculosis and CR3 (31,37), but unambiguous evidence that nonopsonic (i.e., C3bi-independent) interactions occur was obtained in studies in which CR3 was expressed in a nonmacrophage background, so that endogenous synthesis of C3 by macrophages could not interfere. Chinese hamster ovary (CHO) cells stably transfected with CD18 and CD11b bind a strain of M. tuberculosis H37Rv ("CC") in a serum-independent manner, and binding of this strain is not enhanced by fresh human or bovine serum (9). A monoclonal antibody that blocks the C3bi binding site in the I domain of CD11b does not block binding of H37Rv-CC to transfected CHO cells, whereas an antibody to an alternative site within the I domain and an antibody to the C-terminal domain do block binding to CR3 expressed on CHO cells.…”
Section: Complement Receptorsmentioning
confidence: 99%